Identidad entre Ser y Verdad en la filosofía de San Anselmo de Canterbury - Gaona Carrillo, José Luis (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
The thought of St. Anselm of Canterbury from the text of the Proslogion constantly resorts to the methodology entitled fides quarens intellectum. From believing to understanding, it is faith that seeks your intellection. The Proslogion or also known as unum argumentum is an invitation to the reader towards the contemplatio dei. Throughout its XXVI chapters St. Anselm dedicated certain passages, where the so-called "nominations of God" can be found. From this medieval booklet the section dedicated to the Being of God develops argumentatively. Consequently, favoring the search for this identity between Being and Truth, the Anselmian text of De Veritate¸ has been taken because in it Anselm conceptualizes a definition of Truth. Following the different nominations of God in the Proslogion, this identity demonstrates the true character of each one of them. It is the thought who sees a chiastic movement between words and things. Considering some historical elements of the eleventh century, the time of the Holy Doctor Anselmo, the essential motivations and notions of the Proslogion argument are reconstructed, whose objective is to point out an interpretation closer to the true intentions of the Magnificent Doctor. Finally, an aesthetic structural hermeneutical methodology allows from the argumentative discourse to aesthetically capture a medieval symbology. The figure of the cross symbolizes the argument of the Prologion, diagram collected in this investigation of the text If there is God, who is he? The conclusions of the present investigation were not only favorable to this identity between Being and Truth, a new symbolic figure is reached: the holy spirit prostrated in the center of the cross.

El pensamiento de San Anselmo de Canterbury a partir del texto del Proslogion constantemente recurre a la metodología intitulada fides quarens intellectum. Del creer para entender, es la fe que busca su intelección. El Proslogion o también conocido como unum argumentum es una invitación al lector hacia la contemplatio dei. A lo largo de sus XXVI capítulos San Anselmo dedicó ciertos pasajes, donde pueden encontrarse las llamadas “nominaciones de Dios”. De este opúsculo medieval se desarrolla argumentativamente el apartado dedicado al Ser de Dios. En consecuencia, favoreciendo la búsqueda de esta identidad entre Ser y Verdad, se ha tomado el texto anselmiano De Veritate¸ debido a que en éste Anselmo conceptualiza una definición de Verdad. Siguiendo las diferentes nominaciones de Dios en el Proslogion, esta identidad demuestra el carácter verdadero que tiene cada una de ellas. Es el pensamiento quién mira un movimiento quiástico entre las palabras y las cosas. Considerando algunos elementos históricos del siglo XI, época del Santo Doctor Anselmo, se reconstruyen las motivaciones y nociones esenciales del argumento del Proslogion, cuyo objetivo es señalar una interpretación más allegada a las verdaderas intenciones del Doctor Magnífico. Por último, una metodología hermenéutica estructural estética permite desde el discurso argumentativo plasmar estéticamente una simbología medieval. La figura de la cruz simboliza el argumento del Prologion, diagrama recogido en esta investigación del texto ¿Si hay Dios, ¿quién es? Las conclusiones de la presente investigación no sólo fueron favorables a esta identidad entre Ser y Verdad, es alcanzada una nueva figura simbólica: el espíritu santo postrado en el centro de la cruz.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2019-1362; Proslogion; De Veritate; Filosofía medieval; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1636